Pengaruh Tuntutan Pekerjaan dan Sumberdaya Pekerjaan terhadap Turnover Intention dengan Keterikatan Kerja sebagai Variabel Intervening pada Tenaga Kesehatan - Fajriani, Nurul; Suhartini, Eka; Abdullah, Wahidah (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2023)
This research aims to examine the influence of Job Demands, Job Resources on Turnover Intention with Work Engagement as an Intervening Variable. This research is quantitative research with an associative approach. The population in this study were nurses who worked at the Faisal Islamic Hospital in Makassar The sample in this study was 96 nurses taken using the Slovin formula. The data collection method uses a quantitative method, where data collection uses a questionnaire distributed directly from the first source or place where the research object is carried out. Hypothesis testing was carried out using linear regression analysis for hypotheses 1, 2, 3, 4 and 5, path analysis and Sobel test for hypotheses 6 and 7 using the SPSS program The results of this study indicate that Job Demands have a negative effect on Work Engagement, Job Resources have a positive and significant effect on Work Engagement, Job Demands have a positive and significant effect on Turnover Intention, Job Resources have a negative and significant effect on Turnover Intention, Work Engagement has a negative and significant effect on Turnover Intention , Job Engagement can mediate the influence of Job Demands on Turnover Intention and Job Engagement can mediate the influence of Job Resources on Turnover Intention Keywords: Job Demands, Job Resources, Turnover Intention, Job Engagement